ĐÁNH GIÁ HOẠT TÍNH ANDROGEN CỦA BÀI THUỐC “BỔ THẬN SINH TINH THANG” TRÊN CHUỘT CỐNG ĐỰC CHƯA TRƯỞNG THÀNH - Vũ, Trí Linh (Tạp chí Sinh lý học Việt Nam, 2019)
Objective: To study the androgenic activity of “Bo than sinh tinh thang” remedy extract on immature male rats. Method: 8-week-old male Wistar rats, oral “Bo than sinh tinh thang” remedy extract dose of 12.6g/kg/day and 25.2g/kg/day, daily for 28 days. Evaluate weight of rats, weight of sexual organs involved in androgen hormones and testosterone levels in blood of rats. Results: The extract of “Bo than sinh tinh thang” remedy had the effect of increasing blood testosterone levels, increasing the weight of seminal vesicles and levator ani-bulbocavernosus muscle (p < 0.05 compared to control group). Conclution: “Bo than sinh tinh thang” remedy dose of 12.6g/kg/day and 25.2g/kg/day, oral during 28 days, showed androgenic activity when evaluated on immature male rats. Keywords: Bo than sinh tinh thang, androgen, immature male rats.